2022
DOI: 10.3389/fendo.2022.932286
|View full text |Cite
|
Sign up to set email alerts
|

Renal oncometabolite L-2-hydroxyglutarate imposes a block in kidney tubulogenesis: Evidence for an epigenetic basis for the L-2HG-induced impairment of differentiation

Abstract: 2-Hydroxyglutarate (2HG) overproducing tumors arise in a number of tissues, including the kidney. The tumorigenesis resulting from overproduced 2HG has been attributed to the ability of 2HG alter gene expression by inhibiting α-ketoglutarate (αKG)-dependent dioxygenases, including Ten-eleven-Translocation (TET) enzymes. Genes that regulate cellular differentiation are reportedly repressed, blocking differentiation of mesenchymal cells into myocytes, and adipocytes. In this report, the expression of the enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Consistent with this hypothesis, 5hmC blots of genomic DNA derived from primary RPT cells with an L2HGDH KD indicated that the level of 5hmC was reduced in primary RPT cells with an L2HGDH KD (vs. controls) [43]. In addition, Western blots indicated increases in the levels of a number of different classes of methylated histones in primary RPT cells with an L2HGD KD [43]. Not only was there an increase in the level of the activating histone, H3K4me3, but also an increase in the level of the repressive histone H3K27me3.…”
Section: Tablesupporting
confidence: 53%
See 4 more Smart Citations
“…Consistent with this hypothesis, 5hmC blots of genomic DNA derived from primary RPT cells with an L2HGDH KD indicated that the level of 5hmC was reduced in primary RPT cells with an L2HGDH KD (vs. controls) [43]. In addition, Western blots indicated increases in the levels of a number of different classes of methylated histones in primary RPT cells with an L2HGD KD [43]. Not only was there an increase in the level of the activating histone, H3K4me3, but also an increase in the level of the repressive histone H3K27me3.…”
Section: Tablesupporting
confidence: 53%
“…Included amongst these αKG dependent dioxygenases are Jmj-KDM histone demethylases, as well as TET 5mC demethylases, which are inhibited not only in tumor cells with IDH1 and IDH2 mutations [45], but also in ccRCCs with reduced L2HGDH levels [11]. Consistent with this hypothesis, 5hmC blots of genomic DNA derived from primary RPT cells with an L2HGDH KD indicated that the level of 5hmC was reduced in primary RPT cells with an L2HGDH KD (vs. controls) [43]. In addition, Western blots indicated increases in the levels of a number of different classes of methylated histones in primary RPT cells with an L2HGD KD [43].…”
Section: Tablementioning
confidence: 73%
See 3 more Smart Citations